Repurposing of antipsychotic trifluoperazine for treating brain metastasis, lung metastasis and bone metastasis of melanoma by disrupting autophagy flux. (January 2021) - Xia, Yong; Xu, Fuyan; Xiong, Meiping; Yang, Hao; Lin, Wentao; Xie, Yao; Xi, Huizhi; Xue, Qiang; Ye, Tinghong; Yu, Luoting
Graphical abstract: Abstract: Targeted therapies and immunotherapy have brought substantial benefits to patients with melanoma. However, brain metastases remain the biggest threat to the survival and quality of life of melanoma patients. One of the major challenges to an effective therapy is the inability of drugs to penetrate the blood-brain barrier (BBB). Anti-schizophrenic drugs can cross the BBB, and many of them have demonstrated anti-cancer effects. Repurposing existing drugs for new clinical indications is an alluring strategy for anticancer drug discovery. Herein, we applied this strategy and screened a small collection of existing anti-schizophrenic drugs to use as anti-melanoma agents. Among them, trifluoperazine dihydrochloride (TFP) exhibited promising potencies for suppressing the growth and metastasis of melanoma, both in vitro and in vivo . TFP obviously suppressed the viability of melanoma cells within the micromolar range and inhibited the growth of melanoma in the subcutaneous mice models. Notably, intraperitoneal (i.p.) administration of TFP (40 mg/kg/day) obviously inhibited the growth of intra-carotid-injection established melanoma brain metastasis and extended the survival of brain metastasis-bearing mice. Moreover, TFP significantly suppressed lung metastasis and bone metastasis of melanoma in preclinical metastasis models. Mechanistically, TFP caused G0/G1 cell cycle arrest and mitochondrial-dependent intrinsic apoptosis of melanoma cells. In addition, TFP treatment increased the expression of microtubule associated protein 1 light chain 3 beta-II (LC3B-II) and p62 in vitro, suggesting an inhibition of autophagic flux. TFP decreased LysoTracker Red uptake after treatment, indicating impaired acidification of lysosomes. Moreover, the colocalization of LC3 with lysosomal-associated membrane protein 1 (LAMP1), a lysosome marker, was also suppressed after TFP treatment, suggesting that TFP might block the fusion of autophagosomes with lysosomes, which led to autophagosome accumulation. Taken together, our data highlight the potential of repurposing TFP as a new adjuvant drug for treating melanoma patients with brain, lung, and bone metastases.